Prevalence and genetic diversity of Pentatrichomonas hominis in pig populations in Guangdong and Anhui Provinces, China - Lu Pengyun; Zhu Yibin; Cai Haiming; Shen Hanqin; Fang Siyun; Wang Dingai; Yan Zhuanqiang; Liao Shenquan; Qi Nanshan; Lv Minna; Lin Xuhui; Song Yongle; et al. (Parasite)
Pentatrichomonas hominis is a protozoan parasite that infects the gastrointestinal tract of humans and mammals, causing abdominal pain and diarrhea. However, its presence in pigs and its potential as a pathogen causing diarrhea in piglets have not been well studied. This study aimed to investigate the prevalence of P. hominis in pigs and its potential for zoonotic transmission. A total of 406 pig fecal samples were collected from four pig farms located in Guangdong and Anhui Provinces. Fecal DNA extraction was carried out using a commercially available kit. A nested PCR methodology was employed to detect the presence of P. hominis infection. Samples that tested positive were subsequently subjected to sequencing, and the genetic characteristics of the 18S ribosomal RNA (rRNA) gene were analyzed. The overall infection rate of P. hominis was 34.98% (142/406), in Guangdong Province 28.47% (80/281), and in Anhui Province 49.60% (62/125). Among different age groups, suckling piglets had the highest infection rate at 40.24% (68/169). Genetic analysis of the P. hominis isolates showed that the PH-1 genotype was predominant and had a high degree of similarity to P. hominis sequences obtained from humans, cats, and pigs, indicating the potential for zoonotic transmission. The high infection rate and genetic diversity highlight the need for effective control measures in pig farming to reduce parasite transmission and zoonotic risk.